2003
DOI: 10.1562/0031-8655(2003)078<0278:poptwh>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of Photodynamic Therapy with Hypericin by Mitomycin C in the Radiation-induced Fibrosarcoma–1 Mouse Tumor Model¶

Abstract: Hypericin, a polycyclic quinone obtained from plants of the genus Hypericum, has been shown to be a promising photosensitizer. We investigated the combination of hypericin-photodynamic therapy (PDT) and a bioreductive drug mitomycin C (MMC) in the present study. The radiation-induced fibrosarcoma-1 tumors were exposed to laser light (120 J/cm2 at 595 nm) 24 h after an intravenous injection of hypericin (1 mg/kg). Hypericin-PDT alone significantly decreased tumor perfusion and oxygen tension as demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Combining MMC with PDT enables the reduction of both light dose and photosensitizer dose . Geel et al studied the combination of MMC and PDT with three different photosensitizers, meso‐tetrahydroxyphenylchlorin (m‐THPC), bateriochlorin α (BCA) and Photofrin .…”
Section: Combining Phototherapy With Chemotherapymentioning
confidence: 99%
“…Combining MMC with PDT enables the reduction of both light dose and photosensitizer dose . Geel et al studied the combination of MMC and PDT with three different photosensitizers, meso‐tetrahydroxyphenylchlorin (m‐THPC), bateriochlorin α (BCA) and Photofrin .…”
Section: Combining Phototherapy With Chemotherapymentioning
confidence: 99%
“…The combination of Hyp PDT and mitomycin C, a bioreductive compound that is especially toxic to hypoxic cells, was studied in the RIF-1 tumor model by Chen et al [208]. Hyp PDT alone caused about 60% direct cell killing and significant decreases in tumor perfusion and oxygenation.…”
Section: Immunological Aspects Of Hyp-based Pdtmentioning
confidence: 99%
“…Under these conditions, injection of mitomycin C (2.5 mg.kg -1 , 20 min prior to irradiation) significantly potentiated the cytotoxic effect of Hyp PDT and caused delayed tumor re-growth compared to PDT or mitomycin C treatment alone. Therefore, the combination with a bioreductive drug such as mitomycin C is suggested to enhance tumor cell killing under hypoxic conditions and might be useful to achieve selective and effective tumor control [208].…”
Section: Immunological Aspects Of Hyp-based Pdtmentioning
confidence: 99%
“…Many investigations have demonstrated that PDT with hypericin significantly inhibits tumor growth and induces apoptosis or necrosis in different cell lines (5–9). Besides, in vivo studies demonstrated the efficacy of hypericin‐mediated PDT (10,11) and clinical trials have confirmed the potential of hypericin‐PDT for the treatment of recurrent mesothelioma (12) and basal and squamous cell carcinoma (13). Hypericin has been evaluated in phase I/II clinical trials, in glioblastoma multiform patients, in patients with cutaneous T‐cell lymphoma, and in psoriasis (14).…”
Section: Introductionmentioning
confidence: 98%